Ozone observations by the Japanese Antarctic Research Expedition (JARE) - Kouji Matsubara (National Institute of Polar Research, 1997)
Ozone observations by the Japanese Antarctic Research Expedition (JARE) have been carried out since 1961. In the period of the Antarctic Climate Research Project (ACR) new observations were carried out in addition to historical observations using instruments such as Dobson spectrophotometer and ozonesonde. The new observations were as follows : 1) At Syowa Station surface ozone, UV-B radiation, columnar NO_2 and O_3,total ozone and aerosol determined using a Dasibi ozone meter, Brewer spectrophotometer, visible spectrometer, and Polar Patrol Balloon (PPB), respectively, 2) Columnar and vertical ozone amount from the equatorial region to Antarctica on board the research vessel SHIRASE.